Cyclic GMP Balance Is Critical for Malaria Parasite Transmission from the Mosquito to the Mammalian Host - Viswanathan Lakshmanan (American Society for Microbiology, 2015)
ABSTRACT Transmission of malaria occurs during Anopheles mosquito vector blood meals, when Plasmodium sporozoites that have invaded the mosquito salivary glands are delivered to the mammalian host. Sporozoites display a unique form of motility that is essential for their movement across cellular host barriers and invasion of hepatocytes. While the molecular machinery powering motility and invasion is increasingly well defined, the signaling events that control these essential parasite activities have not been clearly delineated. Here, we identify a phosphodiesterase (PDEγ) in Plasmodium, a regulator of signaling through cyclic nucleotide second messengers. Reverse transcriptase PCR (RT-PCR) analysis and epitope tagging of endogenous PDEγ detected its expression in blood stages and sporozoites of Plasmodium yoelii. Deletion of PDEγ (pdeγ−) rendered sporozoites nonmotile, and they failed to invade the mosquito salivary glands. Consequently, PDEγ deletion completely blocked parasite transmission by mosquito bite. Strikingly, pdeγ− sporozoites showed dramatically elevated levels of cyclic GMP (cGMP), indicating that a perturbation in cyclic nucleotide balance is involved in the observed phenotypic defects. Transcriptome sequencing (RNA-Seq) analysis of pdeγ− sporozoites revealed reduced transcript abundance of genes that encode key components of the motility and invasion apparatus. Our data reveal a crucial role for PDEγ in maintaining the cyclic nucleotide balance in the malaria parasite sporozoite stage, which in turn is essential for parasite transmission from mosquito to mammal. IMPORTANCE Malaria is a formidable threat to human health worldwide, and there is an urgent need to identify novel drug targets for this parasitic disease. The parasite is transmitted by mosquito bite, inoculating the host with infectious sporozoite stages. We show that cellular signaling by cyclic nucleotides is critical for transmission of the parasite from the mosquito vector to the mammalian host. Parasite phosphodiesterase γ is essential for maintaining cyclic nucleotide balance, and its deletion blocks transmission of sporozoites. A deeper understanding of the signaling mechanisms involved in transmission might inform the discovery of novel drugs that interrupt this essential step in the parasite life cycle.